Letter - Teignmouth Trades & Labour Council, 7 May 1926 (Teignmouth)
1926-05-07 "Letter - Teignmouth Trades & Labour Council, 7 May 1926" [g0345001.jpg], 7 May 1926, Teignmouth Trades & Labour Council Local Organisation